SEVEN FLAGS ANCESTOR SHRINE - Djuraeva Sanabar Nurmatovna (International Scientific and Current Research Conferences, 2026)
The article “Seven Flags Ancestor Shrine” explores the historical, cultural, and symbolic significance of the Seven Flags Ancestor Shrine as a sacred site dedicated to honoring ancestral heritage. It examines the origins of the shrine, the meaning behind the seven flags as representations of lineage, unity, and spiritual continuity, and the role of the site in preserving collective memory. The study highlights architectural features, ritual practices, and community traditions associated with the shrine, emphasizing its importance as both a spiritual center and a cultural landmark. Through historical analysis and ethnographic perspectives, the article demonstrates how the shrine embodies identity, respect for ancestors, and intergenerational connection.